Predicting the Severity of Acute Pancreatitis Using Ultrasound Markers and Clinical Scales - V. A. Rudenko; L. N. Kakaulina; I. V. Verzakova; I. M. Karamova (Неотложная медицинская помощь)
Abstract For the timely determination of the tactics of treatment of acute pancreatitis, it is necessary to predict the severity when the patient enters the hospital.Aim of the study To assess the possibility of predicting the severity of acute pancreatitis using ultrasound markers, clinical scales.Material and methods A retrospective analysis of the diagnostic results of 84 patients who were hospitalized for acute pancreatitis was carried out. The results of clinical-laboratory and morphological diagnostic methods obtained upon admission of a patient to a hospital in patients with varying degrees of severity of ap were analyzed. Clinical and laboratory data were analyzed using prognostic scales — marshall, ranson, sofa, bisap. The analysis of morphological changes in the pancreas during ultrasound and computed tomography was performed using the balthazar classification.Results The sensitivity of clinical scales for determining the severity of ap was 67% on the sofa scale, 87.5% on the bisap scale, and 100% on the ranson and marshall scales. All patients (22) who had signs corresponding to the balthazar stage d and e upon ultrasound examination subsequently had a moderate and severe course of the disease.Conclusion The use of ultrasonic markers of acute pancreatitis in conjunction with the data of clinical and laboratory scales makes it possible to predict the severity of acute pancreatitis.